Dynamic Changes of Gut Microbiome and Immune Response During the Acute Stage of Stroke in a Pig Model (P14-012-19). (13th June 2019) - Jeon, Julie; Lourenco, Jeferson; Kaiser, Erin; Waters, Elizabeth; Scheulin, Kelly; Fagan, Madison; Fang, Xi; Kinder, Holly; Platt, Simon; Duberstein, Kylee; Rothrock, M; Callaway, Todd; et al.
Abstract: Objectives: Stroke is a leading cause of mortality and disability in the United States. Secondary injuries induced by inflammation plays a critical role in stroke recovery. This study investigates gut microbiome changes during the acute stage of ischemic stroke to better understand the role of gut microbiome in inflammation in an ischemic stroke pig model. Methods: Ischemic stroke was induced by middle cerebral artery occlusion in pigs ( n = 7). Fecal samples were collected at pre-stoke (PRE), 1 (1DPS), 3 (3DPS), and 5 days post-stroke (5DPS) to measure gut microbiome composition. Blood samples were collected at 1DPS for white blood cell analysis. Results: Ischemic stroke was confirmed by magnetic resonance imaging at 1DPS. The dominant pre-stroke fecal bacterial phyla (>1% relative abundance) were Firmicutes (89.2%), Bacteroidetes (3.7%), Actinobacteria (2.0%) and Proteobacteria (1.3%). This composition significantly ( P < 0.05) differed at 3DPS with a decreased Firmicutes (68.1%) and increased Actinobacteria (3.70%) and Proteobacteria (19.0%), and a trending ( P = 0.06) increase among Bacteroidetes (7.6%). At 5DPS, Bacteroidetes (7.6%) remained elevated, but Firmicutes (86.6%), Actinobacteria (2.0%) and Proteobacteria (0.7%) returned to levels similar to PRE. At 1DPS, the α-diversity measured by Shannon index and species evenness were both decreased ( P < 0.05), suggesting that overall bacterial diversity decreased immediately after the stroke. β-diversity analysis showed a trend for overall differences over time ( P = 0.07), but no differences between specific days were found. Elevated inflammation and neutrophil-to-lymphocyte ratio (NLR) following stroke event have been related to negative functional outcome in stroke patients. At 1DPS, a significant increase in NLR was observed in the stroke pigs compared to those at PRE ( P < 0.05), suggesting initiation of inflammatory response following stroke. Conclusions: Ischemic stroke altered the gut microbiome composition, reduced microbiome diversity and increased immune response in pigs. Future studies are warranted to investigate systemic and neural inflammation mediated by the alteration of the gut microbiome following ischemic stroke. Funding Sources: The study was funded by the National Institute of Health and University of Georgia (Faculty Research Grant).